Attitude and awareness of students towards the reference service at the General Reference Section, University of the Philippines Diliman Main Library - Panchadsaram, Madhuram K. 1958-
The study used the survey method to achieve the objectives. The subject of this study are the students who used the U. P. Diliman Main Library during the second semester 1987-88. The students came from different colleges within and outside the Diliman Campus. To get a fair representation, five percent (769) of the total population (15,382) of the U. P. Diliman campus student population were selected to be the respondents for this study. The 769 was considered as population. Out of 769 questionnaires, 678 were returned answered. This constitutes an 88.7 percent return.